DAMPAK DIGITALISASI TERHADAP PERTUMBUHAN EKONOMI MAKRO INDONESIA - Mentari, Chintia Indah; Wahyuni, Fitri; Rahmadani, Putri; Rindiani, Wahyu A; Hendra, Joni (Al-Sharf: Jurnal Ekonomi Islam, 2024)
Economic growth in Indonesia has been the government's main focus in recent decades. Improvements in information and communication technology, especially in the digital era, have played a significant role in changing the overall economic landscape. The research method used in this journal is a research library study which is a library study, meaning that information is collected through the use of library sources, such as literature searches. The digital economy is an engine that drives economic growth in the form of daily economic activities in carrying out buying and selling by carrying out digital transactions and communicating digitally also through the web or marketplace which is part of e-commerce in Indonesia.